The italian action plan for the endangered eurasian otter Lutra lutra - LOY, Anna; BOITANI L; BONESI L; CANU A; DI CROCE A; FIORENTINO P. L; GENOVESI P; MATTEI L; PANZACCHI M; PRIGIONI C; RANDI E; REGGIANI G. (2010)
Although recent evidence of the species recovery has been reported for many European countries, in Italy the Eurasian otter Lutra lutra is still considered endan- gered. Otter populations are confined to few river basins in the southern part of the peninsu- la and these are both geographically and genetically isolated from other European popula- tions. This critical situation led the Italian Ministry of Environment to promote the produc- tion of an Action Plan for the otter in Italy, whose methods, aims and actions are briefly summarized. Nonostante i segnali di recupero segnalati in molti paesi europei, la lontra Lutra lutra è ancora una delle specie più minacciate della fauna italiana, in virtù delle pic- cole dimensionino della popolazione e del suo isolamento , sia geografico, sia genetico, dal resto delle popolazioni europee. Sulla base di queste considerazioni il Ministero dell’Ambiente e della Tutela del territorio e del Mare ha recentemente promosso la realiz- zazione di un Piano d’Azione Nazionale per la Conservazione della Lontra, i cui contenuti, obiettivi, e azioni sono riassunti in questo lavoro.